2022
DOI: 10.1002/mma.8772
|View full text |Cite
|
Sign up to set email alerts
|

Some novel mathematical analysis on the fractional‐order 2019‐nCoV dynamical model

Abstract: Since December 2019, the whole world has been facing the big challenge of Covid‐19 or 2019‐nCoV. Some nations have controlled or are controlling the spread of this virus strongly, but some countries are in big trouble because of their poor control strategies. Nowadays, mathematical models are very effective tools to simulate outbreaks of this virus. In this research, we analyze a fractional‐order model of Covid‐19 in terms of the Caputo fractional derivative. First, we generalize an integer‐order model to a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Our proposed COVID-19 SIR model is positive and bounded. We found that if the basic reproduction number [38] , then COVID-19 will disappear and if [39] , then the disease COVID-19 will remain in the system and will remain stable. Also, when the value of is greater than 1 [40] , COVID-19 will spread and cause an outbreak.…”
Section: Bifurcationmentioning
confidence: 99%
“…Our proposed COVID-19 SIR model is positive and bounded. We found that if the basic reproduction number [38] , then COVID-19 will disappear and if [39] , then the disease COVID-19 will remain in the system and will remain stable. Also, when the value of is greater than 1 [40] , COVID-19 will spread and cause an outbreak.…”
Section: Bifurcationmentioning
confidence: 99%
“…Using dynamical systems described by fractional differential equations (FDEs) has become a way to understand complex materials and processes [10]. FDEs are capable of modeling non-locality, memory, spatial heterogeneity, and anomalous diffusion that are inherent in many real-world problems, making them useful in fields such as dynamical modeling [11], biology [12], chemistry [13], hydrology [14], control, signal and image processing, and finance [15].…”
Section: Introductionmentioning
confidence: 99%
“…In India, 90% of the population has received the first dose, and 70% have been given both doses of the vaccine [15] . However, the COVID-19 vaccines could not offer a 100% protection against the infection due to the discoveries of new variants [16] . This is evident from many cases of post-vaccination infections that have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Owoyemi et al. [16] made a generalization of an integer-order mathematical model describing the transmission dynamics of COVID-19 to a fractional-order version in the sense of Caputo fractional derivative. In a similar study, El-Sayed et al.…”
Section: Introductionmentioning
confidence: 99%